2016
DOI: 10.2134/agronj2016.05.0288
|View full text |Cite
|
Sign up to set email alerts
|

A Model–Data Fusion Approach for Predicting Cover Crop Nitrogen Supply to Corn

Abstract: C over crop use in the mid-Atlantic and other regions of the United States has expanded in recent decades because they are an eff ective tool for reducing erosion and nutrient leaching and because they are a source of recycled N and fi xed N 2 for ecological nutrient management (Drinkwater and Snapp, 2007;Hively et al., 2015). However, it remains a signifi cant challenge to explain the variability and predict the outcome of N cycling processes across a range of cover crop management practices (Ketterings et al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
53
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 42 publications
(80 reference statements)
2
53
0
Order By: Relevance
“…1D). These results are in keeping with previous findings that the mean effect of cover crop mixtures (mostly bicultures) on maize yield is relatively small (Marcillo and Miguez, 2017) and that there is a risk of maize yield loss following high-C/N cover crop mixtures (Kuykendall et al, 2015;White et al, 2016White et al, , 2017.…”
Section: Cash Crop Yieldssupporting
confidence: 92%
See 1 more Smart Citation
“…1D). These results are in keeping with previous findings that the mean effect of cover crop mixtures (mostly bicultures) on maize yield is relatively small (Marcillo and Miguez, 2017) and that there is a risk of maize yield loss following high-C/N cover crop mixtures (Kuykendall et al, 2015;White et al, 2016White et al, , 2017.…”
Section: Cash Crop Yieldssupporting
confidence: 92%
“…A small body of literature indicates that cover crop mixtures can strongly influence the yield of the following crop by affecting soil N availability, particularly for crops with high N demand, such as maize (Kuykendall et al, 2015; Finney et al, 2016; White et al, 2016, 2017). Plant residue with a C/N ratio below 25 is likely to result in net N mineralization when returned to the soil, increasing N supply, while residue with a C/N ratio higher than 25 is likely to result in net N immobilization, reducing soil N supply (White et al, 2016). In a tilled system with no fertilizer added, Finney et al (2016) found that cover crop mixtures with low‐C/N biomass increased maize yield by up to 47%, while high‐C/N mixtures decreased maize yield by up to 70%.…”
mentioning
confidence: 99%
“…by 20 cm deep) per plot were collected and composited for analysis on two dates, before (May) and after (July) cover crop termination. Nitrogen supply was calculated using a previously calibrated model that predicts the effects of cover crop residues and N uptake on N availability to subsequent maize crops, relative to a no‐cover control (White et al, 2016). The model inputs were fall and spring cover crop biomass N per unit area, spring biomass C/N ratio, and spring soil NO 3 − concentrations for each plot.…”
Section: Methodsmentioning
confidence: 99%
“…White et al . (2016) used a model-data fusion approach to predict corn yield response to cover crops. The model uses a humification coefficient based on the C:N ratio of the cover crop residue to predict net mineralization/immobilization for conditions in Pennsylvania.…”
Section: Introductionmentioning
confidence: 99%